2021
DOI: 10.1186/s12913-021-06291-w
|View full text |Cite
|
Sign up to set email alerts
|

Storage management and wastage of reproductive health medicines and associated challenges in west Wollega zone of Ethiopia: a mixed cross-sectional descriptive study

Abstract: Background Keeping proper storage conditions at health facilities is vital to reduce pharmaceutical wastage caused by environmental factors. The expiration of medicines at the health facilities could lead to wastage of potentially life-saving drugs and unnecessary expenditure on the disposal of those expired medicines. Therefore, the aim of this study was to assess pharmaceutical stores and wastage of reproductive health medicines due to expiration in the west Wollega zone of Ethiopia. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
4
2
Order By: Relevance
“…Solid dosage forms (51.99%) and liquid dosage forms (45.34%) were the most commonly expired medicines in value found in the evaluated hospitals. Different study findings reported from the health facilities of the central Oromia region in south-west Shoa (34) and the west Wollega zone (48) revealed that the percentage wastage rate of expired medicines was high (7.5%) and 8.04% as compared to the present study, respectively. However, the findings of the current study were reported as high when compared with a study conducted in Amara region, Dessie town, Ethiopia, which reported that about 3.68% of medicine expired in the health facilities (49).…”
Section: Discussioncontrasting
confidence: 97%
“…Solid dosage forms (51.99%) and liquid dosage forms (45.34%) were the most commonly expired medicines in value found in the evaluated hospitals. Different study findings reported from the health facilities of the central Oromia region in south-west Shoa (34) and the west Wollega zone (48) revealed that the percentage wastage rate of expired medicines was high (7.5%) and 8.04% as compared to the present study, respectively. However, the findings of the current study were reported as high when compared with a study conducted in Amara region, Dessie town, Ethiopia, which reported that about 3.68% of medicine expired in the health facilities (49).…”
Section: Discussioncontrasting
confidence: 97%
“…In our study, 5(83.33%) hospitals fulfilled the criteria of acceptable storage conditions, which is optimal but below the national maximum of 22 and closely similar to the result of the previous survey, in which 80% of hospitals met the acceptable storage conditions. It is higher than a finding in Lesotho (57.43%) 34 but lower than a finding from the west of the Wollega zone that 4(100%) 32 hospitals met storage criteria. The study is not without limitation, and it was limited to public hospitals.…”
Section: Discussioncontrasting
confidence: 62%
“… 31 In this study, the overall wastage rate was 13.1% which is more than twice the national normal, 22 and higher than a similar previous study where wastage due to expiration was 8.04%. 32 The difference from the standard may be attributed to poor adherence to the Federal Hospitals Pharmacy directive 33 and lower commitment of the store managers. Furthermore, medicines stored in acceptable conditions enable the maintenance of the quality of medicines and reduce the wastage of scarce resources.…”
Section: Discussionmentioning
confidence: 99%
“…The highest wasted LC was Acid alcohol and carbol fuchsine, which accounted for 37.5% and 31.3% of their annual budget, respectively. This finding is far above the Ethiopian hospital services transformation guidelines [ 31 ], where the wastage rate should be below 2%, and the study conducted in the West Wollega zone, Ethiopia, 8.04% [ 32 ].…”
Section: Discussionmentioning
confidence: 78%